Purification and Sorting of Halloysite Nanotubes into Homogeneous, Agglomeration-Free Fractions by Polydopamine Functionalization - (:unkn) unknown (AMER CHEMICAL SOC, 2020)
Halloysite nanotubes (HNTs) have attracted great attention in the field of nanotechnology as natural, high value-added nanomaterials. Despite their significant potential as carriers of active agents and fillers in nanocomposite structures, inhomogeneity of HNTs in terms of length and diameter along with their a lomeration tendency poses important obstacles for the utilization of them in a wider range of applications. Here, a facile, three-step separation protocol that allows the sorting of HNTs into agglomeration-free, uniform size fractions is reported. The protocol consists of coating of HNTs with polydopamine to impart hydrophilicity and aqueous dispersibility, followed by their ultrasonication and centrifugation at varying velocities for size-based separation. Particle size distribution analysis by scanning electron microscopy and dynamic light scattering has demonstrated that the separation protocol resulted in uniform HNT fractions of varying agglomeration states and particle sizes. The highest quality fraction obtained with 18% yield was free of agglomerations and consisted of HNTs of uniform lengths and diameters. The polydopamine coating on HNTs which facilitated the separation was demonstrated to be removed by a simple heat treatment that preserved the crystal structure of HNTs. The impact of the separation protocol on the loading and functionalization capacity of halloysites was investigated. Highest quality HNTs presented 4.1-fold increase in lumen loading and 1.9-fold increase in covalent surface coupling ratios compared to the loading and functionalization ratios obtained with raw HNTs. Similarly, sorted, high-quality HNTs were demonstrated to be better dispersed in a polymeric matrix, resulting in polymeric nanocomposites with significantly enhanced mechanical properties compared to nanocomposites prepared with raw HNTs. The three-step separation protocol presented here provides a toolbox that allows sorting of raw HNTs into uniform fractions of different size ranges, from which HNTs of desired qualities required by different applications can be selected.
Keywords: MEMBRANES; NANOCOMPOSITES; SEPARATION